"Of my own accord" : Milton's Dialogue with the Rabbis in Samson Agonistes - Pittman, Joshua W. (East Carolina University, 2014)
This thesis examines rabbinic commentaries on the Samson story and the ways in which Milton appropriates or differs from these interpretations. It considers the critical debate over whether Samson's character and violent life are justified and seeks to reconcile critics who justify Samson with those who vilify him. It argues that seeing Samson as a type of Christ, but an incomplete type, at least partially obviates this dissension by making Samson sinful while also allowing his final action to serve the will of God.
Keywords: British and Irish literature; Religion; Christian tragedy; Rabbis; Tragedy; Violence; Samson Agonistes; Milton, John, 1608-1674--Criticism and interpretation; Milton, John, 1608-1674--Knowledge--Judaism; Milton, John, 1608-1674. Samson Agonistes; Samson (Biblical judge)--In literature; Rashi, 1040-1105; Kimhi, David, approximately 1160-approximately 1235; Levi ben Gershom, 1288-1344; Maimonides, Moses, 1135-1204